The Effect of Video-Assisted Role Playing Using Penglipuran Village Context on Elementary School Students’ Pancasila Education Learning Outcomes - Ni Putu Ayu Gayatri Dewi; Anak Agung Gede Agung; Anak Agung Ayu Dewi Sutyaningsih (Indonesian Journal of Instruction, 2026)
The low learning outcomes in Pancasila Education among elementary school students indicate problems in the learning process, characterized by low student participation, the dominance of lecture-based methods, and the limited use of contextual and engaging learning media. This study aims to analyze the effect of a role-playing learning model assisted by video based on the Pancasila Student Profile on students’ learning outcomes. This research employed a quantitative approach with a quasi-experimental design, specifically a post-test only control group design. The subjects consisted of an experimental group and a control group selected through cluster random sampling. Data were collected using a validated multiple-choice objective test and analyzed using descriptive and inferential statistics through an independent t-test. The results revealed a significant difference between the two groups, where the experimental group achieved higher mean learning outcomes than the control group. These findings indicate that the implementation of a role-playing learning model assisted by video enhances student engagement and promotes more meaningful understanding of concepts. Therefore, this learning model has positive implications as an innovative instructional strategy to improve learning outcomes in Pancasila Education at the elementary school level.